2024
DOI: 10.1158/2767-9764.crc-23-0313
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of the Liposomal Formulation of Eribulin (E7389-LF) in Combination with Nivolumab: Results from the Small Cell Lung Cancer Cohort

Makoto Nishio,
Shuji Murakami,
Hisato Kawakami
et al.

Abstract: Purpose: E7389-LF is a liposomal formulation of eribulin that contributes to tumor vascular remodeling. The phase 2 part of this phase 1b/2 study assessed the efficacy/safety of E7389-LF in combination with nivolumab in several disease cohorts; herein, we report results from the small cell lung cancer (SCLC) cohort. Patients and Methods: Patients with unresectable/measurable SCLC and disease progression with first-line platinum-based chemotherapy with/without an immune-checkpoint inhibitor (ICI) were enrolled … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…There were great expectations of the PARPis; however, taking together the results from the various clinical trials, we can conclude that the activity of these drugs administered alone or in combination with different drugs (CT, ICI and mTKI) is poor in an unselected patient population [ 110 , 134 , 139 , 140 , 141 , 142 , 143 , 144 ]. Some studies reported that SLFN11 is a predictor of response to platinum and PARPis in SCLC [ 12 , 130 , 221 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were great expectations of the PARPis; however, taking together the results from the various clinical trials, we can conclude that the activity of these drugs administered alone or in combination with different drugs (CT, ICI and mTKI) is poor in an unselected patient population [ 110 , 134 , 139 , 140 , 141 , 142 , 143 , 144 ]. Some studies reported that SLFN11 is a predictor of response to platinum and PARPis in SCLC [ 12 , 130 , 221 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the effectiveness of anti-PD-(L)-1, attempts have been made to combine these ICIs with other drugs. In several studies, anti-PD1 was combined with chemotherapy (amrubicin, paclitaxel, gemcitabine, and liposomal formulation [LF]-eribulin) in pretreated patients with SCLC but with limited benefit, as reported in Table S9 [ 139 , 140 , 141 , 142 ]. Two phase II trial evaluated apatinib (anti-VEGFR2) plus camrelizumab (an anti-PDL-1) and anlotinib (a multi-tyrosine kinase inhibitor [mTKI]) plus penpulimab (an anti-PDL-1) [ 143 , 144 ].…”
Section: New Therapeutics In Developmentmentioning
confidence: 99%